A beacon of light : an Amish romance - Byler, Linda (Byler, Linda. Long road home, 2022)
Having nowhere else to go, May decides to return to the Amish community she lived in as a child before her parents died. There she is taken in by Clara, who helps her reintegrate into the community, but she sinks into depression. Will May ever see her brother, Oba, again? How can she heal from her past? Can she ever open her heart to another man?